THE IMPACT OF PERIOPERATIVE FACTORS ON THE OUTCOME IN PATIENTS WITH RUPTURED ABDOMINAL AORTIC ANEURYSM - Čović, Dajana; Stjepanović, Miloš; Majkić, Milan; Tucaković, Dušan; Budakov, Nebojša; Manojlović, Vladimir (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: An aneurysm is a permanent, localized extension of an artery diameter by at least 50% relative to its physiological diameter. Its most common localization is on the abdominal aorta. Rupture, the most common complication of an aneurysm, is clinically significant because of the high mortality rate. Patients with ruptured aneurysm of the abdominal aorta undergo urgent surgical treatment, where despite the efforts of surgeons and expansive progress in both medicine and technology, intraoperative and postoperative mortality is still present in a high percentage. The Aim: To examine how different perioperative factors affect the outcome in patients with ruptured aneurysms of the abdominal aorta. Material and methods: A retrospective study based on medical records for a two-year period, in which descriptive statistical methods processed and analyzed perioperative clinical parameters and their impact on outcome in 57 patients operated on for rupture of abdominal aortic aneurysm. Results: Preoperative values of hemoglobin and components of the hemostasis system, intraoperative blood replenishment and intraoperative pH, and postoperative values of potassium, lactate, and the amount of diuresis in the first 24 hours after surgery showed a statistically significant effect on the outcome in patients operated at the Clinical Center of Vojvodina due to rupture of abdominal aortic aneurysm. Conclusion: The operative outcome in rAAA is still unpredictable despite many years of research into perioperative factors and attempts to find an ideal scoring system.